1996
DOI: 10.1002/(sici)1097-4644(199608)62:2<158::aid-jcb3>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic continuity of nuclear and mitotic matrix proteins in the cell cycle

Abstract: The eukaryotic cell nucleus is a membrane-enclosed compartment containing the genome and associated molecules supported by a highly insoluble filamentous network known as the nucleoskeleton or nuclear matrix. The nuclear matrix is believed to play roles in maintaining nuclear architecture and organizing nuclear metabolism. Recently, advances in microscopic techniques and the availability of new molecular probes have made it possible to localize functional domains within the nuclear matrix and demonstrate dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Several nuclear proteins have been reported to display a specific compartmentalization (e.g., within the nucleolus, nuclear domains, or chromatin), and distribution (e.g., diffuse or aggregated), which change during the cell cycle (3,4), upon a switch between proliferation and growth arrest (5), or after cell differentiation (6)(7)(8)(9). Studies using three-dimensional (3D) culture of breast epithelial cells in the presence of laminin-rich extracellular matrix have revealed that the distribution of certain nuclear proteins depends also on tissue morphogenesis (5,10).…”
mentioning
confidence: 99%
“…Several nuclear proteins have been reported to display a specific compartmentalization (e.g., within the nucleolus, nuclear domains, or chromatin), and distribution (e.g., diffuse or aggregated), which change during the cell cycle (3,4), upon a switch between proliferation and growth arrest (5), or after cell differentiation (6)(7)(8)(9). Studies using three-dimensional (3D) culture of breast epithelial cells in the presence of laminin-rich extracellular matrix have revealed that the distribution of certain nuclear proteins depends also on tissue morphogenesis (5,10).…”
mentioning
confidence: 99%
“…It has been postulated that the nuclear matrix has a role in the expression of genes by concentrating a subset of transcription factors at specific nuclear sites (Stein et al, 1991;Merriman et al, 1995). Transcription factors associated with the nuclear matrix include ER, HET, GATA-1, YY1, AML-1, Spl, Octl, mutant p53, and Rb (Dworetzky et al, 1992;Isomura et al, 1992;Vassetzky et al, 1993;van Wijnen et al, 1993;Merriman et al, 1995;Guo et al, 1995;Müller et al, 1996;Mancini et al, 1996;Kim et al, 1996;.…”
Section: Nuclear Matrix and Processing Of The Genetic Informationmentioning
confidence: 95%
“…These observations are consistent with the idea that alterations in higher order chromatin structure and may, in part, be controlled by disulfide-rich nuclear matrix proteins, [15][16][17][18][19][20][21] which orchestrate widespread changes in restriction enzyme site exposure and sequestration. However, these digestion experiments also suggest that the disulfide-rich nuclear matrix cannot be a static or fixed structure, which is consistent with current models of chromatin structure and higher order nuclear organization of gene regulatory machinery in nuclear matrix-associated microenvironments that support combinatorial control of gene expression by dynamic, physiologically responsive targeting and retention mechanisms.…”
Section: In This Issue Ofmentioning
confidence: 99%